On Freud’s Origin of Religion:A Kalam Jadid Perspective - Muhammad Kholid Muslih; Ahmad Rizqi Fadlilah; Tegar Hafidh Alim (Universitas Darussalam Gontor, 2025)
Sigmund Freud was a figure who had a wide influence. He explained that religion originates from human thoughts. This article aims to further explain Freud’s theory of the origin of religion and analyze it through the perspective of Kalam Jadid. This research is qualitative research with a literature study type. The data obtained are then analyzed interpretively, comparatively, and historically. Following the assessment process, it was discovered that the following points encapsulate Freud’s idea of the genesis of religion. First, totemism is a sort of religion that dates to early tribes. Second, monotheism is one of the faiths that have evolved from earlier ones. Third, people invented religion to get over emotions of helplessness and terror when confronted with difficult life circumstances. Therefore, religion is a type of neurosis as well. According to Kalam Jadid, there are several flaws in Freud’s thesis. There is no hard evidence to back up Freud’s claim that totemism was the first religion. Freud’s premise that God does not exist is also the foundation of his theory. It is implied that Freud disregarded the idea that revelation is a source of knowledge, and that people are inherently religious and have a spiritual side.